Diagnostic Performance of Mac-2-Binding Protein Glycosylation Isomer (M2BPGi), compared to Transient Elastography to Assess Liver Stiffness in Treatment Naïve Chronic Hepatitis C Patients - Andri Sanityoso Sulaiman; Irsan Hasan; Cosmas Rinaldi A Lesmana; Juferdy Kurniawan; Chyntia Olivia Maurine Jasirwan; Saut Nababan; Kemal Fariz Kalista; Rachmadianti Sukma Hanifa; Desti Rachmani; Rino Alvani Gani (Acta Medica Indonesiana, 2023)
Background: Liver fibrosis is an essential factor in the management of Hepatitis C virus infection. Its assessment is crucial in decision-making regarding the therapeutic decisions, and the patients’ follow up. However, the established liver measurement methods have several limitations. Therefore, this study aims to assess the role of Mac-2-Binding Protein Glycosylation Isomer (M2BPGi) as a novel biomarker to measure liver stiffness in treatment naïve Chronic Hepatitis C Indonesian patients. Methods: This study used a cross-sectional design to determine the correlation between serum M2BPGi and the degree of liver stiffness, Transient Elastrography, and differences in serum M2BPGi levels in chronic hepatitis C patients. Serum M2BPGi level and Transient Elastography results were evaluated in 56 Chronic Hepatitis C patients and 48 healthy controls. Pearson correlation analysis was conducted to find the correlation between the level of M2BPGi and Transient Elastography result. ROC analysis was conducted to find the optimum cut-off to assess fibrosis’s degree among Chronic Hepatitis C Patients. Results: The level of serum M2BPGi and Transient Elastography result was strongly correlated with the median level of serum M2BPGi. It was also significantly higher among Chronic Hepatitis C Patients than among healthy controls (r: 0.708, p<0.001; 0.590 COI vs. 4.130 COI, p<0.001). Among the Chronic Hepatitis C patients, the median serum of M2BPGi increased according to the degree of liver fibrosis: 1.500 COI (F0-F1), 2.985 COI (F2-F3) and 8.785 COI (≥F4). The optimum cut-off value for diagnosing significant fibrosis (F2-F3) was 1.820 COI (AUC: 90.8%) and for diagnosing cirrhosis (≥F4) was 3.770 COI (AUC: 89.3%). Conclusion: Serum M2BPGi was a reliable diagnostic tool for identifying liver fibrosis in Indonesian patients with Chronic Hepatitis C.